1992
DOI: 10.1099/0022-1317-73-4-983
|View full text |Cite
|
Sign up to set email alerts
|

The amino terminus of human cytomegalovirus glycoprotein B contains epitopes that vary among strains

Abstract: We mapped three antigenic domains of continuous epitopes on human cytomegalovirus (CMV) glycoprotein B (gB) by reacting a panel of independently derived monoclonal antibodies with deletion mutants expressed transiently in COS-1 cells. One of these antigenic domains, DC2, maps in the last 75 amino acids of the carboxy terminus. These epitopes are conserved in strains Towne and AD169, as well as in 19 clinical CMV isolates. ELISAs of DC2-reactive antibodies with a set of overlapping synthetic oligopeptides from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…The cross-neutralization activity of monoclonal antibodies directed against these epitopes has not been investigated using different clinical HCMV strains. However, it has been shown that binding of monoclonal antibodies and of human serum antibodies to AD2 differs between laboratory and clinical HCMV strains (Meyer et al, 1992 ;Basgoz et al, 1992). Furthermore, codon changes in AD1 and AD2 between clinical strains have been demonstrated (Roy et al, 1993 ;Meyer-Ko$ nig et al, 1998 b ;MeyerKo$ nig et al, 1998 a).…”
Section: Discussionmentioning
confidence: 99%
“…The cross-neutralization activity of monoclonal antibodies directed against these epitopes has not been investigated using different clinical HCMV strains. However, it has been shown that binding of monoclonal antibodies and of human serum antibodies to AD2 differs between laboratory and clinical HCMV strains (Meyer et al, 1992 ;Basgoz et al, 1992). Furthermore, codon changes in AD1 and AD2 between clinical strains have been demonstrated (Roy et al, 1993 ;Meyer-Ko$ nig et al, 1998 b ;MeyerKo$ nig et al, 1998 a).…”
Section: Discussionmentioning
confidence: 99%
“…1 (c). Lumenal orientation of the carboxy-terminal portion has been shown to be unlikely (Basgoz et al, 1992;Fig. 1 c, iv and v).…”
Section: Establishment Of Transfectants Expressing Mutagenized Gb Formsmentioning
confidence: 99%
“…The amino-terminal part of gB, with 19 consensus sequences for N-glycosylation, is thought to be lumenal (Basgoz et al, 1992) and the hydrophilic carboxy-terminal portion of about 130 aa represents the cytoplasmic tail (Spaete et al, 1988, Cranage et al, 1986. In addition, HCMV gB exhibits the particular feature of a consensus sequence for intramolecular proteolytic cleavage at aa 459 (Spaete et al, 1988(Spaete et al, , 1990) by cellular furin (Vey et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Properties of neutralizing MAbs to HCMV gB (UL55), mapping of their epitopes and analysis of neutralization by blocking fusion of the virion envelope with the plasma membrane have been published (Basgoz et al, 1992;Navarro et al, 1993;Pereira et al, 1984Pereira et al, , 1991Qadri et al, 1992). Immunoglobulin (Ig) was purified from murine ascites fuids by Protein A affinity chromatography according to the manufacturer's instructions (Affi-Gel protein A MAPS II Kit; Bio-Rad).…”
Section: Cells Culture Media Viruses and Propagation Of Cells On Pementioning
confidence: 99%